Dapsone Induced Methemoglobinemia in an Adolescent Girl: The Treatment Challenge (Bangladesh Journal of Child Health, 2020)
Dapsone is a sulfone group of antibiotics that works as anti-inflammatory and immunosuppressive agents. It is widely used in many diseases like Acne vulgaris, leprosy, dermatitis herpetiformis, thrombocytopenic purpura, and pemphigoid. Though it is a very cheap drug it has life-threatening side effects like Methemoglobinemia. We hereby report a case of dapsone-induced Methemoglobinemia in an adolescent girl who used dapsone for the treatment of acne vulgaris. She presented with hypoxia, cyanosis, and fatigability. Treatment should be initiated as early as possible otherwise it could be fatal. Here, in this case, immediate treatment was started with vitamin C and N Acytyle cystine as the most effective antidote Methylene blue was not available. As the patient’s condition did not improve with pharmacological treatment so exchange transfusion was done from 2nd day. This case report aims to enhance awareness among physicians about the life-threatening adverse reaction to Dapsone and also the importance of prompt management.Bangladesh J Child Health 2020; VOL 44 (2) :109-113